Effects of specific high resistance training in the water on competitive swimmers - Toussaint, H. M.; Vervoorn, K. (International Journal of Sports Medicine, 1990)
A new training device derived from the MAD system (system to measure active drag, Hollander et al, 8) providing fixed push off points in the water for swimming the front crawl is described. The effects of training on this device (called POP from fixed Push Off Point) are determined by comparing the increase in performance of a training group (N=11) to a control group (N=11). The control group continued the normal training program. During ten weeks the training group followed the same program but 3 times per week sprints performed on the POP were substituted for normal free swimming sprints. Despite the fact that training time and volume were equal, the training group showed a significantly greater improvement in force (from 91 to 94 N, 3.3%), velocity (from 1.75 to 1.81 m•s-1, 3.4%), and power (from 160 to 172 W, 7%) as measured on the MAD system, and an increase in distance per stroke in free swimming. The training group showed a significant improvement in race times for 50 m (from 27.2 to 26.6 s), 100 m (from 59.3 to 57.4 s), and 200 m (from 129.6 to 127.3 s). It is concluded that the POP is a specific training device especially suitable for increasing maximal power output during swimming.